CSF lactate. Issue 4 (13th May 2020) - Baheerathan, Aravindhan; Pitceathly, Robert DS; Curtis, Carmel; Davies, Nicholas WS
Abstract : Lactate is produced from anaerobic glycolysis, which occurs in most tissues in the human body. Blood lactate is tested in most physiologically unwell patients in the Emergency Department and helps to guide treatment and prognosis. Cerebrospinal fluid (CSF) lactate, however, is not often measured. Various central nervous system (CNS) conditions lead to a rise in CSF lactate, including acute neurological infection, stroke, seizures and mitochondrial pathologies. This article discusses the utility and limitations of CSF lactate, highlighting specific clinical situations where it can help in the diagnosis of CNS infections and unexplained encephalopathy.